2017
DOI: 10.1080/10669817.2017.1323607
|View full text |Cite
|
Sign up to set email alerts
|

Does shared decision making results in better health related outcomes for individuals with painful musculoskeletal disorders? A systematic review

Abstract: : Shared Decision-Making (SDM) is a dynamic process by which the health care professional and the patient influence each other in making health-related choices or decisions. SDM is strongly embedded in today's health care approaches, and is advocated as an ideal model since it renders individuals more control towards the health care they choose to receive, and has been shown to improve patient outcomes. : The goal of this systematic review was to investigate the added-value of SDM on clinical health-related ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…There are some studies that suggest that SDM (measured with other tools) might be associated with better outcomes related to decisional conflict and patient satisfaction but it is unclear whether this relates to clinical outcomes …”
Section: Introductionmentioning
confidence: 99%
“…There are some studies that suggest that SDM (measured with other tools) might be associated with better outcomes related to decisional conflict and patient satisfaction but it is unclear whether this relates to clinical outcomes …”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the term ‘Shared Decision Making’ (SDM) has gained increasing attention in physiotherapy research (Hoffmann et al, 2014; Parsons et al, 2012; Topp, Westenhöfer, Scholl, & Hahlweg, 2017; Tousignant‐Laflamme et al, 2017), with a recent claim that it should be an integral part of physiotherapy practice (Hoffmann, Lewis, & Maher, 2020). Shared Decision Making can be defined as: A consultation process where a clinician and patient jointly participate in making a health decision, having discussed the options and their benefits and harms, and having considered the patient's values, preferences and circumstances (Hoffmann et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a Swedish qualitative study on physiotherapy for musculoskeletal problems, all participants described a preference for participating in the clinical decision making process (Bernhardsson, Larsson, Johansson, & Öberg, 2017). In contrast, a systematic review reported a lack of studies showing a true effect on patient reported outcomes and questions the efficacy of SDM in a population with musculoskeletal pain (Tousignant‐Laflamme et al, 2017). This conclusion is supported by a recent clustered randomized controlled trial (RCT) with patients with low back pain.…”
Section: Discussionmentioning
confidence: 99%
“…These have been labeled consumerist, informative, informed, autonomous, or engineering models [3,7,[13][14][15][16]. Despite being touted as the ultimate model, several systematic reviews of shared decision making reveal a dearth of supportive evidence, leaving their impact on empirical health outcomes uncertain [10,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%